Assessment of Clinical Outcomes in Patients Presenting with Transverse Myelitis: A Tertiary Care Experience from a Developing Country - Ali, Aijaz (Cureus, 2019)
Background: Transverse myelitis (TM) is an inflammatory disorder of spinal cord, characterized by acute or sub-acute dysfunction of spinal cord affecting the motor, sensory, and autonomic systems. It may be idiopathic or related to other diseases. Although some patients recover from TM with minor or no residual problems, others suffer permanent impairments that affect their ability to perform ordinary tasks of daily living. Our objective was to determine the frequency of different clinical outcomes in patients presenting with TM. Methods: It was a prospective cohort clinical study conducted from May 2018 till October 2018. Study was conducted in the Department of Neurology at Jinnah Medical College Hospital (JMCH), Karachi. In total 131 patients of TM were enrolled and treated as per standard protocol, and re-evaluated after eight weeks for assessment of clinical outcomes. Results: The average age of patients was 51.15 ± 6.56 years. Out of 131 cases, 36.6% of patients had full recovery and 63.4% had poor recovery while recurrence occurred in 66.7% cases. Urinary frequency was observed in 12.2% cases and incontinence in 6.9% cases. Conclusion: Acute TM has become transformed with recent developments, especially the advent of the MRI and the discovery of biomarkers.